Building Bridges Across Borders: Networked Learning within the International Community of Online Schools (ICONS) - Declercq, Lieselot; Declercq, Annabel; Verlaeckt, Koen (Proceedings of the International Conference on Networked Learning, 2026)
This short paper examines how networked learning can enhance collaboration, inclusion, and professional exchange among online schools. Drawing on data from a 2024–2025 ICONS survey, the study explores pedagogical models, shared challenges, and collaboration priorities within the International Community of Online Schools (ICONS), a global network initiated by d-teach online school (Belgium). ICONS brings together 19 K–12 online schools across Europe and beyond, collectively reaching learners in more than 90 countries worldwide, and serving thousands of globally mobile, multilingual, and special-needs students. The research adopts a mixed-methods design combining descriptive statistics and thematic analysis of open-ended responses. Findings reveal a professional and diverse ecosystem of online schools that blend synchronous and asynchronous learning, prioritize humanized digital pedagogy, and explicitly link their missions to SDG 4 and UNESCO’s principles on digital inclusion. While 46.7% of participating schools provide official diplomas, they often operate within fragmented policy systems that fail to recognize their transnational educational role. Three central collaboration priorities emerged from the survey: (1) pedagogical innovation and AI integration to humanize technology in education, (2) quality assurance and cross-border recognition, and (3) teacher professional development through shared modules and peer learning. These findings are interpreted through the lens of Networked Learning theory (de Laat & Dohn, 2019; Networked Learning Editorial Collective, 2021a, 2021b), which conceptualizes learning as a relational process distributed across people, organizations, and technologies. Within this framework, ICONS functions as a networked ecosystem enabling schools to learn with and from one another, transforming isolated innovation into collective intelligence. The paper argues that online schools should not be viewed as substitutes for traditional schooling, but as pedagogically rich and socially connected extensions of educational opportunity that provide continuity and inclusion for learners whose education is disrupted by mobility, geography, health constraints, or other reasons. Policy recommendations call for inclusive recognition frameworks that value online schools as equal partners within education systems, alongside European-level professional development programmes that build teacher capacity in digital pedagogy and AI literacy. By situating online schooling within a networked learning paradigm, this study contributes to ongoing debates on equity, recognition, and collaboration in postdigital education. ICONS exemplifies how distributed professional communities can foster innovation and inclusion across borders, advancing the vision of a more connected and resilient global education ecosystem.